2021
DOI: 10.2147/ijgm.s320711
|View full text |Cite
|
Sign up to set email alerts
|

Sero-Prevalence and Associated Factors of Hepatitis B Virus Among Pregnant Women at North West Ethiopia: An Institution-Based Cross-Sectional Study

Abstract: Background Hepatitis B virus is a public health problem in the world. It is a major cause of chronic hepatitis, cirrhosis, and hepatic cellular carcinoma. The presence of a confirmed HBsAg result is indicative of ongoing HBV infection. This study aims to assess the sero-prevalence and associated factors of the hepatitis B virus among pregnant women in North West Ethiopia. Methods and Materials An institution-based cross-sectional study was conducted at Debre Markos Refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
5
4
0
Order By: Relevance
“…The seroprevalence of HBsAg in the current study was 8.1% (10/124), and this rate of infectivity can be considered a highly endemic scenario of the virus [ 31 ]. The seroprevalence of HBsAg in the present study was comparable with other similar studies conducted in Ethiopia [ 18 , 26 , 32 ]. A cross-sectional study in Tanzania also reported consistent HBV infection rates among pregnant women [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The seroprevalence of HBsAg in the current study was 8.1% (10/124), and this rate of infectivity can be considered a highly endemic scenario of the virus [ 31 ]. The seroprevalence of HBsAg in the present study was comparable with other similar studies conducted in Ethiopia [ 18 , 26 , 32 ]. A cross-sectional study in Tanzania also reported consistent HBV infection rates among pregnant women [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…In some situations, even pregnant women may not be aware of their HBV serostatus [22], and only a few of the study participants had knowledge about HCV and HBV [23]. The two viral hepatitis seroprevalences among pregnant women become increased through the course of time in different localities of Ethiopia and various parts of Africa [6,[23][24][25][26]. On the contrary, viral hepatitis showed a decreasing pattern in certain developed countries like China [27].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pregnant women who had a history of blood transfusion were 9.3 times more likely of being infected by HBV than pregnant women who had no history of blood transfusion (AOR = 9.3 95% CI (1.57-55.10), p-value = 0.014). This is in line with similar studies conducted in Khairpur teaching hospital, Pakistan [18], Debre markos, Ethiopia [19] and in Tanzania [20]. This is explained due the fact that the virus is transmitted through any body fluids such as mucosal, blood contact from an infected individuals easily.…”
Section: Seroprevalence Of Hepatitis B Virus Infection In the Study P...supporting
confidence: 90%
“…Studies in Ethiopia indicated that the seroprevalence of HBsAg among pregnant women ranged from 2.3% to 8.3%. 21 , 22 However, studies on the prevalence and associated factors among pregnant women particularly in the study area are limited. Therefore, this study aimed to assess the prevalence and factors associated with HBV infection among pregnant mothers who attended ANC at Hawassa city public hospitals.…”
Section: Introductionmentioning
confidence: 99%